2013
DOI: 10.1152/jn.00209.2013
|View full text |Cite
|
Sign up to set email alerts
|

Continuous theta burst transcranial magnetic stimulation reduces resting state connectivity between visual areas

Abstract: Research to date has focused on the effect of cTBS on the target area, but less is known about its effects on the resting state functional connectivity between different brain regions. We investigated this issue by applying cTBS to the occipital cortex and probing its influence in retinotopically defined regions in early visual cortex using functional MRI. We found that occipital cTBS reliably decreased the resting state functional connectivity (i.e., the correlation of spontaneous activity) between regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 49 publications
6
79
3
1
Order By: Relevance
“…Additionally, we have previously reported that cTBS to aI/fO and dlPFC in this subject group led to increases in functional connectivity across widespread multi-modal regions in lateral frontoparietal and cingulate regions [53]. However, two recent studies add to the varied findings seen in resting state functional connectivity results when combined with rTMS: Chen and colleagues [77] found similar decreases in the functional connectivity of the default mode network after inhibitory 1 Hz stimulation of two different frontal regions (however, no changes were seen in the stimulated network and this remote decrease can not be distinguished from changes in functional connectivity that might occur naturally over time) and Rahnev and colleagues [78] found decreased connectivity during rest among visual regions after occipital compared with vertex cTBS. Here we add to this previous work by showing how local changes (measured with rCBF) are related to these network-wide effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have previously reported that cTBS to aI/fO and dlPFC in this subject group led to increases in functional connectivity across widespread multi-modal regions in lateral frontoparietal and cingulate regions [53]. However, two recent studies add to the varied findings seen in resting state functional connectivity results when combined with rTMS: Chen and colleagues [77] found similar decreases in the functional connectivity of the default mode network after inhibitory 1 Hz stimulation of two different frontal regions (however, no changes were seen in the stimulated network and this remote decrease can not be distinguished from changes in functional connectivity that might occur naturally over time) and Rahnev and colleagues [78] found decreased connectivity during rest among visual regions after occipital compared with vertex cTBS. Here we add to this previous work by showing how local changes (measured with rCBF) are related to these network-wide effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our previous work [53], a handful of past studies have examined the effect of rTMS on resting state connectivity ([24][26], [77], [78], reviewed by [55]). Two of these studies only found relatively minor changes in the functional connectivity of a small set of regions remote to the stimulation site (in the form of both increased functional connectivity [25] and decreased connectivity [24]).…”
Section: Discussionmentioning
confidence: 99%
“…We fit the models to the data as previously (Rahnev et al, 2011(Rahnev et al, , 2013Rahnev, Maniscalco, Luber, Lau, & Lisanby, 2012) using a maximum likelihood estimation approach. The models were fit to the full distribution of probabilities of each .…”
Section: Model Fittingmentioning
confidence: 99%
“…It is thus likely that pre- and post-TMS resting-state fMRI designs are more sensitive (although less specific) to TMS induced effects. As inter-session interval amounted to at least one week in our study, performing pre- as well as post-TMS scanning sessions, as done in several previous studies [45,42,44,39,43,47,46], might have been able to reduce inter-session variability. Another concern is related to the timing of our resting-state session, as cTBS effects on the BOLD signal are strongly time-dependent.…”
Section: Discussionmentioning
confidence: 92%